Simusol: simulating thermal systems using Sceptre and Dia - Alia de Saravia, Dolores (2003)
This paper shows how two specific programs Sceptre and Dia have been used to develop Simusol, a tool for simulating thermal systems. The thermal system must be outlined with Dia which has to be extended with a specially prepared thermal circuit sheet. The resulting XML Dia-file is translated, by Simusol, into several text files, one of them with input data for Sceptre to simulate the system. Using output from Sceptre, Simusol prepares text files with input data for Gnuplot to represent results. So, in some sense, Simusol converts graphics to code to simulate de system. All the used software, Simusol included, is free; most of it distributed under the GPL license: GNU/Linux, Dia —which works with XML and SVG files—, Sceptre, Perl, f2c, gcc and Gnuplot.